Diagnostic criteria for temporomandibular disorders (DC/TMD) for children and adolescents: An international Delphi study—Part 1‐Development of Axis I. (19th May 2021) - Rongo, Roberto; Ekberg, EwaCarin; Nilsson, Ing‐Marie; Al‐Khotani, Amal; Alstergren, Per; Conti, Paulo Cesar Rodrigues; Durham, Justin; Goulet, Jean‐Paul; Hirsch, Christian; Kalaykova, Stanimira I.; Kapos, Flavia P.; Komiyama, Osamu; et al.
Abstract: Background: Since in children and adolescence prevalence is assessed mainly on self‐reported or proxy‐reported signs and symptoms; there is a need to develop a more comprehensive standardised process for the collection of clinical information and the diagnosis of TMD in these populations. Objective: To develop new instruments and to adapt the diagnostic criteria for temporomandibular disorders (DC/TMD) for the evaluation of TMD in children and adolescents. Method: A modified Delphi method was used to seek international consensus among TMD experts. Fourteen clinicians and researchers in the field of oro‐facial pain and TMD worldwide were invited to participate in a workshop initiated by the International Network for Orofacial Pain and Related Disorders Methodology (INfORM scientific network) at the General Session of the International Association for Dental Research (IADR, London 2018), as the first step in the Delphi process. Participants discussed the protocols required to make physical diagnoses included in the Axis I of the DC/TMD. Thereafter, nine experts in the field were added, and the first Delphi round was created. This survey included 60 statements for Axis I, and the experts were asked to respond to each statement on a five‐item Likert scale ranging from 'Strongly disagree' to 'Strongly agree'. Consensus level was set at 80% agreement for the first round, and at 70% for the next. Results: After three rounds of the Delphi process, a consensus among TMD experts was achieved and two adapted DC/TMD protocols for Axis I physical diagnoses for children and adolescents were developed. Conclusion: Through international consensus among TMD experts, this study adapted the Axis I of the DC/TMD for use in evaluating TMD in children and adolescents. Abstract : The Delphi process included three round and was used to was used to seek international consensus for Axis I assessment among 23 TMD experts. Thanks to this Delphi study, experts developed new instruments that aim to assess physical diagnoses (Axis I) of TMDs in children and in adolescents, by modifying the DC/TMD for adults.